Monitoring non-pharmaceutical public health interventions during the COVID-19 pandemic - Yannan Shen; Guido Powell; Iris Ganser; Qulu Zheng; Chris Grundy; Anya Okhmatovskaia; David L. Buckeridge (Scientific Data, 2021)
Measuring and monitoring non-pharmaceutical interventions is important yet challenging due to the need to clearly define and encode non-pharmaceutical interventions, to collect geographically and socially representative data, and to accurately document the timing at which interventions are initiated and changed. These challenges highlight the importance of integrating and triangulating across multiple databases and the need to expand and fund the mandate for public health organizations to track interventions systematically.